The UK Aircraft Noise Index Study: 20 Years on. - Brooker, Peter (Institue of Acoustics, 2004)
In the early 1980s the UK Department of Transport (now the Department for Transport: DfT is used here to cover all its incarnations) commissioned a study to determine what index should be used to assess aircraft noise disturbance near major airports. This Aircraft Noise Index Study – ANIS – was completed in 1984 and published shortly afterwards (Brooker et al – ‘ANIS Report’ 1). This study included extensive social surveys and noise measurements around these airports, plus detailed statistical analyses. The main result of the study was that Leq (A weighted) would be an appropriate index. Following publication of the ANIS Report, consultation, and some further work 2, the decision to use the 16-hour Leq for the UK aircraft noise index was announced in September 1990. The standard calculation method is described in Ollerhead et al 3. This paper reviews the methodology of the ANIS work and the subsequent criticisms of ANIS and Leq, with the hindsight of 20 years. Obviously, with such a large subject, it is only possible to give a flavour of the material, so reference should be made to the source documents regarding detailed questions. Unless otherwise noted, references are to data in the ANIS Report.